2020
DOI: 10.18860/mec-j.v4i2.8803
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motivation, Discipline, Job Satisfaction on Female Lecturer Performance at PH University

Abstract: This study intended to determine the impact of motivation, discipline, job satisfaction to performance of women lecturers of PH private university. The background of this study because women lecturers who have motivation, discipline, job satisfaction is expected to show their best performance. The study was conducted with quantitative methods, using questionnaires with five Likert scales distributed to 100 women lecturer from PH private university. Respondents had worked for at least two years as a permanent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Value of path coefficient = 0.952 and P Values = 0,000 < 0.05, meaning effect of motivation (X3) to employee performance is positive and significance. This result supported previous studies by (Rizal et al, 2014), (Sasongko, 2018) and (Meilani et al, 2020). Meaning respondents as lecturers or academic staff feel that motivated to carrying out their duties properly to do their role well in maintaining performance.…”
Section: Discussionsupporting
confidence: 90%
“…Value of path coefficient = 0.952 and P Values = 0,000 < 0.05, meaning effect of motivation (X3) to employee performance is positive and significance. This result supported previous studies by (Rizal et al, 2014), (Sasongko, 2018) and (Meilani et al, 2020). Meaning respondents as lecturers or academic staff feel that motivated to carrying out their duties properly to do their role well in maintaining performance.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the results study of Fu and Deshpande (2014) also show that job satisfaction has a positive effect on employee performance. According to Meilani, Bernarto, Berlianto (2020), job satisfaction is an emotional state that is pleasant or unpleasant for employees to view their work. This shows that the higher the level of job satisfaction of a person, it will also increase the performance of that person, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wibowo (2014), defining job satisfaction is an attitude towards a person's job, which they see is an award that is received and expected or should be. According to Meilani, Bernarto, Berlianto (2020), there are a number of job satisfaction indicators, namely: 1) The Work Itself. If the job is indeed liked, it will be an indicator of job satisfaction; 2) Salary.…”
Section: Introductionmentioning
confidence: 99%
“…The study on female lecturers at Pelita Harapan University conducted by Meilani et al (2020) found that job satisfaction affects performance, meaning that the more satisfied a female lecturer is with aspects of her job, the higher her performance in carrying out the university's three pillars of education, research, and community service, and achieving its goals.…”
Section: The Role Of Work Life Balance In Job Satisfactionmentioning
confidence: 99%